2021
DOI: 10.3354/meps13670
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nutritional state, sex and body size on the marine migration behaviour of sea trout

Abstract: The sea trout (anadromous brown trout Salmo trutta) displays extensive among-individual variation in marine migration behaviour. We studied the migration behaviour of 286 sea trout (27-89 cm) tagged with acoustic transmitters in the spring, in 7 populations located in 2 distinct marine fjord systems in Norway. We examined whether individual nutritional state, sex and body size influenced marine migration behaviour in terms of (1) the decision to migrate to the sea or remain resident in freshwater and/or estuar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 66 publications
0
16
1
Order By: Relevance
“…In general, the tagged individuals remained close to their presumed home river during the marine feeding migration. The restricted migratory distances observed here (< 7 km) were much smaller than observed in other tracking studies of brown trout (typically 15–30 km) in marine fjord habitats 24 , 25 , 27 , 28 . Brown trout generally remain in near-coastal areas during their seaward migrations, close to their river of origin (< 80 km), and on the Patagonian Continental Shelf, brown trout have never been reported in the catch record further than 50 km from their rivers of origin 65 .…”
Section: Discussioncontrasting
confidence: 73%
See 4 more Smart Citations
“…In general, the tagged individuals remained close to their presumed home river during the marine feeding migration. The restricted migratory distances observed here (< 7 km) were much smaller than observed in other tracking studies of brown trout (typically 15–30 km) in marine fjord habitats 24 , 25 , 27 , 28 . Brown trout generally remain in near-coastal areas during their seaward migrations, close to their river of origin (< 80 km), and on the Patagonian Continental Shelf, brown trout have never been reported in the catch record further than 50 km from their rivers of origin 65 .…”
Section: Discussioncontrasting
confidence: 73%
“…While marine migrations are risky, energetic demands driven by the costs of reproduction and growth may determine whether or not a fish moves to sea. It has been shown that individual brown trout, particularly females with low somatic energy stores in spring-time, will migrate further away from the home watercourse to search for prey and facilitate nutritional and somatic re-conditioning 27 , 28 , 74 . Therefore, it might be predicted that these far-ranging individuals are more likely to encounter and explore new freshwater habitats.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations